How do we strengthen the health workforce in a rapidly developing high-income country? A case study of Abu Dhabi's health system in the United Arab Emirates - Marília Silva Paulo; Tom Loney; Luís Velez Lapão (BMC, 2019)
Abstract Background The United Arab Emirates (UAE) is a rapidly developing high-income country that was formed from the union of seven emirates in 1971. The UAE has experienced unprecedented population growth coupled with increased rates of chronic diseases over the past few decades. Healthcare workers are the core foundation of the health system, especially for chronic care conditions, and the UAE health workforce needs to be fully prepared for the increased rates of chronic diseases in the adult population. Abu Dhabi is the largest emirate in terms of land mass and population size, and the purpose of this paper was to assess how the health system has been using the Chronic Care Model to improve its capacity to reach out to all patients in the population. Case presentation The Abu Dhabi health workforce has twice the number of doctors (52.4 vs. 23.2 per 10 000 population) and nurses (134.7 vs. 50.4 per 10 000 population) compared to the entire UAE health workforce. In addition to an overreliance on expatriate workers, there is an excess of some specializations such as general medicine and gynecology and a severe undersupply of other specialties including trauma and injury, and medical oncology. The digital infrastructure and skills of the health workforce need to be improved to minimize the proportion of the appointment time required to complete administrative tasks for a health insurance system and maximize the doctor-patient face-to-face interaction time for consultation and lifestyle counseling. Conclusions A greater emphasis needs to be placed on developing self-management support strategies using a combination of nurse health educators and community-based patient-led health programs. The UAE Vision 2021 includes developing a world-class healthcare system, and full implementation of the Chronic Care Model seems to facilitate the detailed planning and preparation of healthcare services and workers required to achieve this goal.